Cyber security of a power grid: State-of-the-art. (July 2018) - Sun, Chih-Che; Hahn, Adam; Liu, Chen-Ching
Highlights: A review of cyber systems in a smart grid is provided with a list of the communication standards. Requirements for cyber security and industry practice are discussed. The state-of-the-art cyber protection and cyber-physical system testbeds are summarized. The proposed methodology for detection of coordinated cyber attacks is demonstrated. Unsolved cyber vulnerabilities that require future research are described. Abstract: The integration of computing and communication capabilities with the power grid has led to numerous vulnerabilities in the cyber-physical system (CPS). This cyber security threat can significantly impact the physical infrastructure, economy, and society. In traditional IT environments, there are already abundant attack cases demonstrating that unauthorized users have the capability to access and manipulate sensitive data from a protected network domain. Electric power grids have also heavily adopted information technology (IT) to perform real-time control, monitoring, and maintenance tasks. In 2015, a sophisticated cyber attack targeted Ukrainian's power grid causing wide area power outages. It highlights the importance of investment on cyber security against intruders. This paper provides a state-of-the-art survey of the most relevant cyber security studies in power systems. It reviews research that demonstrates cyber security risks and constructs solutions to enhance the security of a power grid. To achieve this goal, this paper covers: (1) a survey of the state-of-the-art smart grid technologies, (2) power industry practices and standards, (3) solutions that address cyber security issues, (4) a review of existing CPS testbeds for cyber security research, and (5) unsolved cyber security problems. Power grid cyber security research has been conducted at Washington State University (WSU) with a hardware-in-a-loop CPS testbed. A demonstration is provided to show how the proposed defense systems can be deployed to protect a power grid against cyber intruders.